A study of the Japanese policy on Islam and Malay-Muslim community during its occupation of Malaya, 1941-1945 - Mohamad Firdaus bin Mansor Majdin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Japanese occupation of Malaya is considered to be a departure point in Malaysia's history which marked a shift of a new colonial master from British to Japanese. In the context of Malaya, following the successful Japanese subjugation of the land in February 1942, the High Command in Tokyo had issued a number of directives to be implemented in the occupied areas including Malaya. The High Command in Tokyo, among others had specified that regional commanders need to respect the natives' religion and folk customs in the occupied areas. As far as Islam is concerned, the Japanese Military Administration seemed to depart from Tokyo's orders in its dealing with Islam and Malay-Muslims as a whole. It seemed that the Japanese had no well-planned policy on Islam and Malay-Muslims in Malaya, nor were they sensitive to Islam and relevant issues concerning Islam and Muslims in the country. Rather Islam was used for propaganda purposes such as the frequent presence of Japanese officials in surau or mosques precinct for mobilizing people' support and the usage of surau or mosques as storehouses in certain occasions. Moreover, the existing literature in the field has not yet sufficiently covered a number of issues evolved around the Japanese policy on Islam and Malay-Muslim in Malaya. My research aims to examine and analyze those issues in order to cater any relevant discussion related to this topic. In doing so, I will use extensive archival documents in this study, which are be in the forms of government records and documents such as annual reports, publications and newspaper reports. Personal accounts in the form of memoirs or diaries will also be utilized in order to assess and examine the attitude of Malay-Muslims toward Japanese administration. Perhaps the letter of correspondence between individuals or organizations will also be instrumental in providing the necessary information in examining the above issues.